Estudió de Factibilidad para la Implementación de una Empresa Productora y Comercializadora de Aliño con Tamarindo en la Ciudad de Loja - Guzmán Celi, Lesly Katherine (2018)
The present research work was carried out in the City of Loja, with the objective of presenting a proposal for the implementation of a tamarind-producing and marketing company for dressing. Among the objectives that was raised is to conduct the market study to know the current demand, supply and demand unmet, perform the technical study to determine the macro and micro location, present an organic-functional proposal of the company to be implemented, and finally, carry out a financial study to establish the investment and financing of the project in order to determine the feasibility or not of the project under study. In the technical study the macro and micro localization of the company is manifested, the installed and used capacity is detailed, the manpower that is needed for the production. The location of the company will be easily accessible to the public because it does not need special infrastructure and is a non-polluting company; that is why it will be located in the neighborhood of Sta. Teresita in the streets Abraham Lincon and José M Carrera corner. In what corresponds to the administrative organization, a company of limited responsibility has been raised, it is made known the hierarchical levels, organizational charts and function manuals that the company will manage to define activities and tasks that the personnel must perform on a daily basis. The Engineering, aims to become a micro-company, with feasible investments for the amount, which is supported by the facilities provided by financial institutions for the promotion of the company. A considerable proportion of the analysis is dedicated to defining the amount of fixed assets, whose sum is $ 3420 deferred assets, whose amount is $ 808.00 feasible for a small group of investors, and Working capital of $ 3893, 42 dollars. The company will be constituted legally, as "LIMITED COMPANY" and has in the investigation, the Organizational Manuals, sufficient to recognize hierarchy and functions of the members. Finally, the evaluation of the project was carried out to establish the suitability of the project and its execution, for which the following indicators were analyzed, such as the Financial Evaluation, the present project has the following indicators: Net Present Value of $ 97,315.64 Internal Rate of Return of 325.06%; Benefit Cost Ratio is $ 1.64 5 for every dollar invested the company earns 0.64 cents; Period of Capital Recovery is 3 months and 23 days; Sensitivity analysis indicates that the project supports an increase in the costs of 54.5% giving a total of 0.95% and sensitivity analysis in the decrease in income of 33.5% giving a total of 0.97%, for which the project is feasible, whose conclusions and recommendations as well they determine it, attaching the bibliography consulted with their respective annexes.